2005
DOI: 10.1387/ijdb.052011he
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus laevis FoxE1 is primarily expressed in the developing pituitary and thyroid

Abstract: The members of the FoxE subfamily of Fox (forkhead) genes are expressed in the developing pituitary, thyroid and lens. Mammalian Foxe1 is expressed primarily in the developing pituitary and thyroid gland, Foxe3 is expressed in the developing lens, while Xenopus FoxE4 is expressed in the developing lens and thyroid. Here we report the identification of Xenopus FoxE1, a gene that is primarily expressed in the developing pituitary and thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Dexamethasone (Dex) was added at late gastrula stage (stage 12-13), and expression of Dmrt5 and Dmrt4, was assayed by in situ hybridization at stage 25-26. In addition to Dmrt4 and Dmrt5, we also examined expression of the otic placode marker Hes2 (Sölter et al, 2006), the pituitary marker FoxE1 (El-Hodiri et al, 2005) and the lens marker FoxE3 (lens1) (Kenyon et al, 1999). We observed that Otx2 overexpression causes at both stages moderate ectopic expression of Dmrt5 and Dmrt4 in the epidermis (75%, n¼57 for Dmrt5 and 41%, n¼37 for Dmrt4) (Fig.…”
Section: Dmrt5 Expression Overlaps With Dmrt4 In the Developing Olfacmentioning
confidence: 99%
“…Dexamethasone (Dex) was added at late gastrula stage (stage 12-13), and expression of Dmrt5 and Dmrt4, was assayed by in situ hybridization at stage 25-26. In addition to Dmrt4 and Dmrt5, we also examined expression of the otic placode marker Hes2 (Sölter et al, 2006), the pituitary marker FoxE1 (El-Hodiri et al, 2005) and the lens marker FoxE3 (lens1) (Kenyon et al, 1999). We observed that Otx2 overexpression causes at both stages moderate ectopic expression of Dmrt5 and Dmrt4 in the epidermis (75%, n¼57 for Dmrt5 and 41%, n¼37 for Dmrt4) (Fig.…”
Section: Dmrt5 Expression Overlaps With Dmrt4 In the Developing Olfacmentioning
confidence: 99%
“…FOXE1 orthologs have additional domain expressions other than in developing thyroid. For instance, frog foxe1 is expressed both in the developing thyroid and pituitary [9]. Foxe1 of zebrafish is expressed in pharyngeal skeleton, gills and thyroid [10].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Xenopus embryo, foxe1 is expressed in the developing thyroid, pituitary mesoderm of brachial arches and the pharyngeal endoderm [9]. In the zebrafish embryo foxe1 is expressed in the thyroid, pharynx, and pharyngeal skeleton [10].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-mount ISH was performed as previously described [19]. Digoxygenin (DIG)- labeled antisense RNA probes (Roche Diagnostics, Indianapolis, IN) were synthesized using template cDNA encoding Anos1, Snai2 [20], Sox10 [21], Sox2 [22], Six1 [23], Foxi4.1 [24], Dmrta1 [25], Pax8 [26], Emx2 [27], Ebf2 [28] and Foxe1 [29]. …”
Section: Methodsmentioning
confidence: 99%